Corporate governance and performance of medium-sized firms in Nigeria: does sustainability initiative matter? - Adedeji, Babatunji Samuel; Ong, Tze San; Hossain, Md Uzir; Abdul Hamid, Abu Bakar (Emerald Group Publishing, 2020)
Purpose: The non-existence of the corporate governance (CG) concept for practices by non-financial medium-sized firms (MSFs) in Nigeria informed. This study aims to determine whether CG practices influence firms’ performance and whether sustainability initiative (SI) mediates the relationship between CG and MSFs’ performance in Nigeria. Design/methodology/approach: A total of 300 firms were selected on convenience sampling basis from South Western Nigeria using a structured questionnaire. The authors used Statistical Package for Social Sciences for exploratory data analysis and hypotheses were tested using covariance-based structural equation modelling. Findings: The results show that CG has a significant positive effect on performance [financial performance (FNP) and non-financial performance (NFP)] and SI. SI has a mixed impact on performance, e.g. a significant positive impact on NFP but insignificant negative impact on FNP. Similarly, SI has a combined mediating effect in the relationship between CG and performance, e.g. fully mediates CG → NFP and does not mediate CG → FNP. Firms are to invest in social and environmental initiatives substantially. CG codes will complement the International Financial Reporting Standards for MSFs. Research limitations/implications: This study supports the assumptions of theories (institutional, stakeholder and agency) as the basis for the usage of multiple approaches to determine the outcome of hypotheses, especially in developing climes. Practical implications: The study contributes to CG and performance literature by examining the mediating effects of SI. The paper also shows the necessity to emphasise NFP aspect. Policymakers should evolve CG codes to encourage stakeholders to believe more in the corporate existence of MSFs for strengthening capital-base and quality personnel engagement. Originality/value: To the best of the authors’ knowledge, this is one of the first empirical attempts showing the evidence on the relationship between CG and NFP in Nigeria.